Taxonomic and Ecological Interaction of Leishmaniasis Vectors (Diptera: Psychodidae) in Sefrou Province (Middle Atlas Morocco). (12th September 2022) - Talbi, Fatima Zahra; Taam, Abdelkarim; El Omari, Hajar; Hilali, Said; Fadil, Mouhcine; El Khayyat, Fatiha; Najy, Mohamed; Mrani Alaoui, Meryem; El-Akhal, Fouad; Alami, Abdellatif; Amaiach, Rachid; Lahouiti, Khadija; et al.
Abstract : An entomological survey was carried out in the locality of Aichoune to conduct a study on sand flies, species composition, and monthly relative abundance. This study is essential for the implementation of integrated vector management control. Insects collection was carried out twice a month from January 2013 to December 2014 by means of adhesive and CDC-type light traps. A total of 5441 sand flies were collected with the predominance of males (a sex ratio = 1.89). The sampled specimens consist of seven species divided into two genera: Phlebotomus (99.55%) and Sergentomyia (0.44%). Phlebotomus sergenti was the dominant species with an average annual proportion of 47.38%, followed by P. perniciosus (37.32%), P. longicuspis (8, 56%), P. papatasi (6.23%), and P. ariasi (0.05%). The genus Sergentomyia was less common (0.44%). S.minuta was represented only by 0.36% and S. fallax by 0.07%. The species dynamics showed a unimodal evolution for P. sergenti and P. papatasi . They were active from May to October. P. perniciosus presents a trimodal trend showing the most relevant peak in August. The highest number of specimens was collected in June, when the temperature reaches an annual average value of 25.5°C. The obtained results will help us better understand the leishmaniasis transmission dynamics in the Aichoune locality and will contribute to the design of a surveillance strategy.